2015
DOI: 10.1111/apha.12487
|View full text |Cite
|
Sign up to set email alerts
|

The median preoptic nucleus: front and centre for the regulation of body fluid, sodium, temperature, sleep and cardiovascular homeostasis

Abstract: Located in the midline anterior wall of the third cerebral ventricle (i.e. the lamina terminalis), the median preoptic nucleus (MnPO) receives a unique set of afferent neural inputs from fore-, mid- and hindbrain. These afferent connections enable it to receive neural signals related to several important aspects of homeostasis. Included in these afferent projections are (i) neural inputs from two adjacent circumventricular organs, the subfornical organ and organum vasculosum laminae terminalis, that respond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
122
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 204 publications
(453 reference statements)
1
122
0
3
Order By: Relevance
“…However, we showed that individual thirst-related neuronal populations of the lamina terminalis are hierarchically organized, and that MnPO nNOS neurons are the behavioural output neurons. Previous lesion studies in rats and sheep have proposed a model in which the MnPO serves as a critical site that integrates inputs from osmosensory neurons of the SFO and the OVLT 3638 . Our findings well explain and further advance the concept of this model with cell-type-specific precision.…”
Section: Discussionmentioning
confidence: 99%
“…However, we showed that individual thirst-related neuronal populations of the lamina terminalis are hierarchically organized, and that MnPO nNOS neurons are the behavioural output neurons. Previous lesion studies in rats and sheep have proposed a model in which the MnPO serves as a critical site that integrates inputs from osmosensory neurons of the SFO and the OVLT 3638 . Our findings well explain and further advance the concept of this model with cell-type-specific precision.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to maternal behavior, the MPOA has a number of important homeostatic roles, including thermoregulation, sleep, and social reward (21,22). Potentially, maternal behavior could be impacted if losing the influence of prolactin on these functions also impaired pregnancyrelated adaptations in the maternal brain.…”
Section: Discussionmentioning
confidence: 99%
“…Males: inIGF1RKO, n = 5, and controls, n = 5; females: inIGF1RKO, n = 8, and controls, n = 8. *P < 0.05; **P < 0.01; ***P < 0.001. structures integrating and controlling thermoregulation in the central nervous system (34). Several areas in POA, for instance, ventrolateral preoptic nucleus (35), receive afferents from forebrain circuitry; namely, through the lateral septal nucleus, but also directly from cortical areas.…”
Section: Discussionmentioning
confidence: 99%